Genetic characterization of group C rotavirus isolated from a child hospitalized with acute gastroenteritis in Chiang Mai, Thailand - P. Khamrin (2018)
During an epidemiological survey of human rotavirus infection in Chiang Mai, Thailand, from 2002 to 2004, in which 263 stool specimens tested, one isolate of group C rotavirus was detected from a two-year-old child admitted to hospital with acute gastroenteritis. The human group C rotavirus, named CMH004/03, was characterized further by molecular analyses of its VP4, VP6, and VP7 gene segments as well as determination of RNA pattern by polyacrylamide gel electrophoresis (PAGE). Molecular characterization of VP4, VP6, and VP7 genes by sequence analyses showed high levels of sequence identities with those of human group C rotavirus reference strains isolated worldwide at 95.2% to 99.4% on nucleotide and 97.5% to 100% on amino acid levels. In contrast, the CMH004/03 strain exhibited far lesser nucleotide and amino acid sequence identities at 67.7% to 84.1% and 68.7% to 91.3%, respectively, when compared with those of porcine and bovine group C rotaviruses. Phylogenetic analyses of VP4, VP6, and VP7 genes clearly confirmed that the CMH004/03 strain clustered in a monophyletic branch with other human group C rotavirus reference strains and distantly related to the clusters of animal group C rotavirus strains. In addition, the RNA electrophoretic migration pattern of CMH004/03 showed a typical pattern (4-3-2-2) of group C rotavirus. To our knowledge, this study is the second report of group C rotavirus infection in pediatric patients in Thailand after it was reported for the first time about two decades ago. © 2008 Springer Science+Business Media, LLC.